Edukasi Pengembangan Media Pembelajaran Visual “Sahabat Unik” Aspek Kognitif, Afektif, dan Psikomotorik Siswa di TK Islam Al-Abrar Desa Teberau Panjang - , (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2023)
Learning media is a tool or intermediary that is used to facilitate the teaching and learning process, in order to streamline communication between teachers and students. This is very helpful for teachers in teaching and makes it easier for students to receive and understand lessons. This process requires teachers who are able to align between learning media and learning methods. The use of learning media in the teaching and learning process can also generate new desires and interests for students, generate motivation to learn, and even have a psychological influence on students. Besides being able to increase student learning motivation, the use or use of media can also increase students' understanding of the lesson. The media used has a position as a teacher's tool in teaching. For example graphics, films, slides, photos, and learning using computers. Its purpose is to capture, process, and reconstruct visual and verbal information. As a tool in teaching, the media is expected to provide concrete experience, motivation to learn, enhance the absorption and retention of student learning.